2010
DOI: 10.1590/s1516-18462010005000019
|View full text |Cite
|
Sign up to set email alerts
|

Índice percentual de reconhecimento de sentenças no silêncio e no ruído: efeitos da aclimatização no indivíduo avaliado sem as próteses auditivas

Abstract: OBJETIVO: verificar o efeito da aclimatização no reconhecimento de sentenças no silêncio e no ruído, em novos usuários de próteses auditivas, avaliados sem as mesmas, antes e após o período de aclimatização. MÉTODOS: participaram do estudo 40 indivíduos, idade entre 28 e 78 anos, que possuíam perda auditiva neurossensorial de grau leve a moderadamente severo, e estavam iniciando o processo de seleção e adaptação de próteses auditivas. Os testes foram realizados em diferentes sessões: antes da adaptação das pró… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…In the ISRPN research, the presentation of sentences remained adjusted on the value obtained in SRTN found for each individual (10) . Two indexes, one with noise at 0º/0º azimuth and another with noise at 0º/180º azimuth were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…In the ISRPN research, the presentation of sentences remained adjusted on the value obtained in SRTN found for each individual (10) . Two indexes, one with noise at 0º/0º azimuth and another with noise at 0º/180º azimuth were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Já na pesquisa do IPRSR, o nível de apresentação das sentenças permaneceu fixo na relação S/R obtida com base nos LRSR encontrados para cada indivíduo 16 . Os IPRSR foram pontuados considerando como erro somente a(s) palavra(s) omitida(s) ou repetida(s) de maneira incorreta 17 .…”
Section: Avaliação Das Habilidades Auditivasunclassified
“…The strategy previously used to study SRI was to set the intensity of the presentation speech (5)(6)(7)(8)10,(15)(16)(17)(18)(19)(20) and present, at the same intensity, all sentences from a list, considering as correct answer, all sentences repeated correctly and as incorrect answer, a whole word or phrase incorrectly repeated (16) . Thus, each error or score corresponded to 10%, respectively, for each list is composed of 10 sentences.…”
Section: Old Strategymentioning
confidence: 99%
“…Thus, after calculating the intensity found in SRTQ for each individual, it was maintained fixed (20) , and the Sentence Recognition Indexes in Quiet (SRIQ) were then obtained using the lists 1B, 2B, 3B, 4B, 5B, and 6B.…”
Section: Application and Analysis Of The New Strategy Proposalmentioning
confidence: 99%
See 1 more Smart Citation